PENGARUH LITERASI KEUANGAN SYARIAH, HEADING BEHAVIOR, DAN RELIGIUSITAS PADA GENERASI Z DAN MILENIAL TERHADAP MINAT INVESTASI DI PASAR MODAL SYARIAH - Harahap, Anggriani Muliadin; Hascaryani, Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
In recent years, the Indonesian capital market has continued to increase and is dominated by generation Z and millennials, both sharia and conventional capital markets. In this modern era, investing has become a trend. Therefore, the author examines whether Islamic financial literacy, herding behavior, and religiosity can influence the interest of generation Z and millennials to invest in the Islamic capital market. This type of research is quantitative research and data was collected from a questionnaire survey using 200 respondents. The data analysis method used is the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS) approach using SmartPLS software. The results of this research are that herding behavior and religiosity have a significant effect on the investment interest of generation Z and millennials in the sharia capital market, while sharia financial literacy has no significant effect. The implication of this research is that these three factors are taken into consideration by potential investors and readers when making investment plans. This research can contribute to the development of the Islamic capital market by providing a better understanding of the perceptions and interests of generation Z and millennials towards the Islamic capital market.